EXPERIENCE OF USING THE RETROSPECTIVE METHOD IN PSYCHOLOGICAL RESEARCH - Семиченко, Валентина; Артюшина, Марина (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2024)
The article is devoted to the problem of diagnostics of individual changes occurring in the psyche of people in conditions of various kinds of social crises. The purpose of the article is the theoretical and empirical justification of the use of the method of retrospection for processing the data of psychological research. This method is based on the awareness of a person of the changes occurring in his psyche, comparing the current self-perception (introspective analysis) with the one in which he perceived himself in the past. The article reveals in detail the essence and features of the method of retrospective analysis, shows the advantages of its use for studying dynamic processes under conditions when in the time perspective the opportunity to use the longitudinal method of organizing the research was lost. The procedure for applying the method of retrospection for the analysis of students' value orientations as a system-forming factor of the structure of the personality and the person's relations with the surrounding world is described. The method of M. Rokich was used for the diagnostics of value orientations. Individual features and trends in the transformation of the value sphere of specific students were identified and an ideographic analysis of their specificity was conducted. As a result of the study, the feasibility and methodological and technical features of introducing a retrospective approach into the practice of conducting psychological research, taking into account the time perspective of analysis, were proven and the corresponding recommendations were given. Based on the analysis of the results obtained on the basis of a combination of introspective and retrospective self-analysis by students of their value orientations, conclusions were formulated on the possibility and prospects of conducting further research using the retrospection method.